Dampak Sistem Informasi Akuntansi Terhadap Kinerja Suplai Agensi - Ahmad Saipudin; Erwan Nurhidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The research aims to explore the impact of SIAs on agency supply performance related to inventory management, customer welfare, operating costs and financial statements. In today's digital age and globalization, AIS is very important, especially in that marketing agencies are responsible for product distribution and their supply performance is crucial. SIAs help agencies manage inventory, monitor suppliers, and expedite deliveries. The implementation of SIA requires HR competence, technology investment, and management support. Research into the effect of SIAs on supply performance is important to improve agency understanding and success. This research contributes to the ongoing discourse on the effectiveness of AIS, offers guidance for optimal implementation and utilization, as well as helps identify areas of improvement to improve organizational performance. This study used explanatory research method with primary and secondary data. Random sampling techniques are used with Pearson correlation and simple linear regression to examine the relationship and influence between each variable. This research shows that the relationship and influence between these variables can be easily examined. Research findings show that SIAs have a positive and significant influence on inventory management, financial statements, customer welfare, and organizational performance. In addition, there is a negative relationship between AIS and operating costs. In this study, it was revealed that AIS has a significant and positive influence on organizational performance. The findings of this study provide recommendations to companies to adopt SIA to improve the performance of their organizations.